2020
DOI: 10.1080/19415257.2020.1742187
|View full text |Cite
|
Sign up to set email alerts
|

A socio-constructivist approach to developing a professional learning intervention for early childhood education and care practitioners in Wales

Abstract: In 16 Flying Start early childhood education and care (ECEC) settings within a Local Authority in Wales, observations of adult-child interactions, using the Sustained Shared Thinking and Emotional Wellbeing Scale (SSTEW), highlighted that interactions that support children's problem solving, curiosity, concept development, and higher-order thinking were the least well developed aspects of practice. A two-day professional learning intervention 'Talking Science', underpinned by a socio-cultural understanding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…The epistemological position of social constructionism is suited to considering the socio-cultural context of the participants and their experiences, which aligns with the foundations of narrative approaches. 41 , 50 A narrative semi-structured interview method was used as per Fernández-Balboa and González-Calvo. 51 , 52 This method uses open questions while keeping the research topic area in mind and asking questions on this area of interest.…”
Section: Methodsmentioning
confidence: 99%
“…The epistemological position of social constructionism is suited to considering the socio-cultural context of the participants and their experiences, which aligns with the foundations of narrative approaches. 41 , 50 A narrative semi-structured interview method was used as per Fernández-Balboa and González-Calvo. 51 , 52 This method uses open questions while keeping the research topic area in mind and asking questions on this area of interest.…”
Section: Methodsmentioning
confidence: 99%
“…We might understand this response as the respondent holding a view that 'Science', as a defined body of knowledge, is relevant for older children and/or inaccessible to young children. Once 'Science' (capital 'S' Science) was re-framed, in the PL programme, as early and exploratory concept development (small 's' science), enhanced through play and playful talk including metacognitive modelling, it became not only accessible for the practitioners (see Tinney et al 2020) but also -in their eyes -for the children. We conjecture that this shift in perspective about the nature of 'Science'/ science may also have been associated with a shift in the perceived relevance of this activity to the children accessing the settings.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 12 studies used integrative research methods, including systematic reviews, narrative reviews and literature reviews, to synthesise the existing literature and identify future research directions ( Howitt et al, 2020;Christenson et al, 2020;Fenrich, 2022). A total of nine studies used a descriptive research design to provide detailed descriptions of PjBL implementation, student experiences and outcomes (Gealy et al, 2022;Jamali et al, 2023). Nine studies used qualitative research methods to explore the experiences and perceptions of students and teachers involved in PjBL through interviews, observations and content analysis (Das, 2020;Kallery et al, 2022;Goos et al, 2023).…”
Section: Research Design and Methodologymentioning
confidence: 99%
“…Resource-rich schools are able to provide more diverse project options and deeper exploration opportunities. Studies have shown that children in resource-rich environments perform significantly better in PjBL than resource-poor environments (Howitt et al, 2020;Gealy et al, 2022).…”
Section: Influence Of Variablesmentioning
confidence: 99%